2020
DOI: 10.1139/bcb-2019-0041
|View full text |Cite
|
Sign up to set email alerts
|

Current approaches for RNA-labelling to identify RNA-binding proteins

Abstract: RNA is involved in all domains of life, playing critical roles in a host of gene expression processes, host-defense mechanisms, cell proliferation, and diseases. A critical component in many of these events is the ability for RNA to interact with proteins. Over the past few decades, our understanding of such RNA–protein interactions and their importance has driven the search and development of new techniques for the identification of RNA-binding proteins. In determining which proteins bind to the RNA of intere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 120 publications
(176 reference statements)
0
17
0
Order By: Relevance
“…One commonly used concept for purification of RNP complexes involves the addition of an RNA aptamer tag to the RNA of interest, which permits capturing the tagged RNA with a high-affinity ligand ( Figure 1). A variety of RNA aptamers are available, and the reader is referred to a recent review further describing RNA-aptamers and RNA labeling techniques [42]. Essentially, two classes of RNA aptamers are commonly used, either binding to small molecules or to proteins.…”
Section: Affinity Capture Of Rnas Via Aptamersmentioning
confidence: 99%
See 1 more Smart Citation
“…One commonly used concept for purification of RNP complexes involves the addition of an RNA aptamer tag to the RNA of interest, which permits capturing the tagged RNA with a high-affinity ligand ( Figure 1). A variety of RNA aptamers are available, and the reader is referred to a recent review further describing RNA-aptamers and RNA labeling techniques [42]. Essentially, two classes of RNA aptamers are commonly used, either binding to small molecules or to proteins.…”
Section: Affinity Capture Of Rnas Via Aptamersmentioning
confidence: 99%
“…A second class of aptamers includes short RNA hairpins that interact specifically with proteins, such as the coat proteins from the R17/MS2 bacteriophage [49], bacterial streptavidin S1 [50], the PP7 coat protein [51], the lambda bacteriophage anti-terminator protein N (or lambdaN peptide) [52], an engineered version of the Csy4 endonuclease [53], or artificial pentatricopeptide repeat (PPR) proteins [54]. While this class of RNA aptamers has been broadly used to globally determine proteins/RNAs interacting with the tagged RNAs in vitro (e.g., [52,55]; reviewed in [36,42,56]); the RNA aptamers and interacting proteins have also been coexpressed in vivo to recover endogenously formed RNP complexes from cell lysates through affinity capture [49,[57][58][59]. For example, RBP purification and identification (RaPID) implemented the affinity purification of MS2 aptamer-tagged RNAs and detection of bound proteins and transcripts with MS and reverse transcription (RT)-PCR, respectively [49].…”
Section: Affinity Capture Of Rnas Via Aptamersmentioning
confidence: 99%
“…When designing RNA-tag-based purification, several considerations need to be considered. The choice of a small tag with high affinity and specificity is favored to avoid interference with the folding and structure of the coat protein, and to apply stringent washes (e.g., using washing buffers containing high salt and detergent concentrations) to remove nonspecific binders [48]. Furthermore, the expression level of the coat protein relative to the RNA expression level and the number of stem loop repeats is critical to achieve the best signal-to-noise ratio.…”
Section: Rna Taggingmentioning
confidence: 99%
“…To execute such a variety of functions, RNA often interacts with proteins. To aid in the discovery of novel RNA-binding proteins, a review article by Gemmill et al (2019) discusses overall approaches to RNAlabelling methods, and provides insights into the benefits/ drawbacks of these methods. Interferon-inducible proteins, which are key components of our innate immune system, recognize viral double-stranded RNA and polymerize ATP to an unusual 2=-5= linked oligoadenylate chain to subsequently activate ribonuclease L. Koul et al (2019) studied one of the key interferon inducible proteins, human 2=-5= oligoadenylate synthetase 2 (OAS2) and demonstrated that both OAS2 domains are essential for polymerizing ATP.…”
Section: Introduction To a Special Issuementioning
confidence: 99%